A review on Holland's career theory - Arokianathan, Nathynie; Zainudin, Zaida Nor; Mohamad Yusop, Yusni (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Holland’s Theory is about people and environment. Holland developed RIASEC model, which is applied to personality types and environment. This systematic review explores on how Holland’s Theory is applied in various researches and aims to explore the effects of using Holland’s Theory and RIASEC model on the research participants. Journal articles were sourced from ProQuest electronic database and Google Scholar. Only research articles in the form of quantitative research are included in this systematic review. Moreover, articles only in English language are used. Subject area related to counselling is included, which are Counselling and Career Development Planning. The countries of the articles in this systematic review are from various countries, namely United States, United Kingdom, Italy, Korea, Nigeria, Pakistan, and Belgium. 10 journal articles extracted were reviewed. Results showed the application of Holland’s theory on researches to examine career aspects and related variables. Various effects of Holland’s Theory and RIASEC model towards participants, including benefits and effects on various variables. Implications of RIASEC towards career counselling and other related aspects were discussed, vastly bringing awareness among career counsellors and related mental health professionals to use RIASEC model of Holland due to the benefits it provides to the society. Moreover, Holland’s theory is also a pioneer in the field of career counselling and career related researches.